Computational Fluid Dynamic Analysis of a Supersonic Turbine - Bacchi, Federico (2015)
The purpose of this work is to study numerically the flow in a supersonic axial flow impulse turbine. Computations were made with Ansys 15 CFD package, with a 3-dimensional model of one stator-rotor stage. The software implements a “mixing plane model” at the interface between the stator domain, which is stationary, and the rotor domain, which is rotating at a prescribed angular velocity, allowing computing each region separately. The flow information between these domains will be coupled at the mixing plane interface.